(untitled) (Indian Journal of Child Health, 2019)
Background: Injectable vaccines are a common source of pain and distress for newborn babies. Sweet-tasting solutions such assucrose and 25% dextrose (25D) are described as effective strategies for pain relief in newborns. Objective: This study was doneto compare the analgesic efficacy of expressed breast milk (EBM) and 25D solution during vaccination with hepatitis B (Hep B)vaccine at birth. Materials and Methods: This study was conducted at the vaccination clinic in the pediatrics department of atertiary care hospital in southern India. The participants included healthy term babies and late preterm babies at the clinic duringtheir routine dose of Hep B at birth, during the study period from June 2017 to December 2017. A total of 70 consecutive neonateswere randomly allocated into two groups. 2 ml of either EBM or 2 ml of 25D solution was given 1 min before the injection. Theoutcome variables recorded were the duration of cry after injection and Neonatal Infant Pain Scale (NIPS) scores for both thegroups. Results: The duration of cry was found to be slightly higher in the group receiving EBM than those receiving 25D, althoughit was not found to be statistically significant. The neonates in the 25D group had lower NIPS scores than those in the EBM group.Conclusions: 25D appears to be a slightly better analgesic when compared to EBM during Hep B injection at birth.